Solve 5/4 - 7/6 - (-2/3)
Answers
Answered by
1
Answer:
x = -8
Step-by-step explanation:
5/4 - 7/6 = (-2/3)
-2 = 24(-2/3)
x = -24(-2/3) / 2
-12(-2/3) = x
-24 / 3 = x
x = -8
Answered by
0
Answer:
There is being a confusion of the two - sign placed before 2/3. I'll solve it in both case of one - sign and two - sign.
1st case : => 5 /4 - 7/6 - 2/3
TAKING LCM,
=> ( 5 x 3 - 7 x 2 - 2 x 4) /12
=> ( 15 - 14 -8) / 12
=> (1 - 8) /12 => -7/12
2nd case:
=> 5/4 - 7/6 - (-2/3 )
=> 5/4 - 7/6+ 2/3
TAKING LCM,
=> (5 x 3 - 7 x 2+2 x 4) /12
=> ( 15 - 14 + 8) / 12
=> (1+ 8) /12
=> 9/12
=> 3/4
TAKING LCM,
=> (5 x 3 - 7 x 2 + 2 x 4) /12
=> ( 15 - 14 + 8) / 12 => (1+ 8) /12
=> 9/12
=> 3/4
HAVE A LOOK AT THE ANSWER YOU WERE LOOKING FOR...
HOPE IT HELPS
Step-by-step explanation:
please mark me as brainliest ☺️
Similar questions